MANAJEMEN EMOSI GURU DALAM PENGELOLAAN KELAS: STUDI KUALITATIF TENTANG STRATEGI MENGATASI PERILAKU AGRESIF PESERTA DIDIK - Vicensia Araya Reinita; Kintan Limiansih; Gracendy Aluz Clarita Budiono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on teachers' emotional management strategies in addressing aggressive student behavior in the classroom, particularly at the elementary school level. The central issue examined is how teachers implement the five components of emotional management as proposed by Daniel Goleman, self-awareness, self- regulation, motivation, empathy, and social skills, in responding to the frequent occurrence of aggressive behavior in learning environments. This research employs a descriptive qualitative approach, using observation and in-depth interviews with three teachers from a private elementary school in the Special Region of Yogyakarta. To ensure data validity, source triangulation techniques were applied. The findings reveal that teachers are capable of recognizing and managing their own emotions through strategies such as deep breathing, remaining silent, or adopting a personalized approach to students. Intrinsic motivation rooted in spiritual, professional, and moral values serves as the primary driving force in maintaining emotional control. Teachers also demonstrate empathy by understanding students' backgrounds and establishing supportive and personal communication. Social skills are reflected in flexible and adaptive approaches to building positive relationships with aggressive students. In conclusion, the five components of emotional management play a crucial role in enabling teachers to create a conducive learning environment and maintain emotional resilience in the classroom. It is recommended that emotional management training and institutional support be continuously enhanced to strengthen teacher professionalism.